2016
DOI: 10.3390/rs8121003
|View full text |Cite
|
Sign up to set email alerts
|

Digital Mapping of Toxic Metals in Qatari Soils Using Remote Sensing and Ancillary Data

Abstract: After decades of mining and industrialization in Qatar, it is important to estimate their impact on soil pollution with toxic metals. The study utilized 300 topsoil (0-30 cm) samples, multi-spectral images (Landsat 8), spectral indices and environmental variables to model and map the spatial distribution of arsenic (As), chromium (Cr), nickel (Ni), copper (Cu), lead (Pb) and zinc (Zn) in Qatari soils. The prediction model used condition-based rules generated in the Cubist tool. In terms of R 2 and the ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 61 publications
3
42
1
Order By: Relevance
“…Meanwhile, total organic carbon (TOC) was 4.1 ± 0.08%, whereas the total inorganic carbon, nitrogen, and hydrogen stood at 8.8 ± 0.04, 0.06 ± 0.33, and 0.48 ± 0.05%, respectively, revealing the soil to be neutral and saline in nature, suggesting low organic matter and high iron and clay components (Usman et al, 2019). The physicochemical characteristics reflect typical Qatari soil known for its high calcium-magnesium carbonates composition (Peng et al, 2016).…”
Section: Analysis Of Physical and Chemical Parametersmentioning
confidence: 77%
See 1 more Smart Citation
“…Meanwhile, total organic carbon (TOC) was 4.1 ± 0.08%, whereas the total inorganic carbon, nitrogen, and hydrogen stood at 8.8 ± 0.04, 0.06 ± 0.33, and 0.48 ± 0.05%, respectively, revealing the soil to be neutral and saline in nature, suggesting low organic matter and high iron and clay components (Usman et al, 2019). The physicochemical characteristics reflect typical Qatari soil known for its high calcium-magnesium carbonates composition (Peng et al, 2016).…”
Section: Analysis Of Physical and Chemical Parametersmentioning
confidence: 77%
“…In this study, ICP-OES results confirm the presence of the metals Cd, Cr, Cu, Ni, and Pb in different concentrations in the soil and plant tissues collected at Mesaieed industrial area. Previous work by Peng et al (2016) and Usman et al (2019) reported the distribution of the same metals on Qatari soil. Overall, ICP-OES data indicates that while Cr was the highest concentrated metal in the soil, all metals, except the barely detectable Cd, bioaccumulates in plants with a preferential concentration in the root.…”
Section: Discussionmentioning
confidence: 92%
“…The antioxidant system is essential for shielding plants against heavy metal toxicity and does so by creating changes in the activities of critical enzymes including catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX), glutathione reductase (GR), and guaiacol peroxidase (GPX) 6 . SOD is the first line of defense; it sequesters noxious superoxide ions and breaks them into less harmful hydrogen peroxide (H 2 O 2 ) and oxygen molecules (O 2 ).…”
mentioning
confidence: 99%
“…Mapping for finding toxic metals has been previously done for different countries. Peng et al [33] have recently done similar mapping projects for the soils of Qatar. Peng et al's research [33] focused on different parameters (soil and groundwater), the mapping approach outlined here are similar.…”
Section: Methodsmentioning
confidence: 99%
“…Rapid structures to support the water treatment systems composed of carbon fibre reinforced fibre structures [15][16][17][18] can also be used. Furthermore, the impacts of climate change are likely to exacerbate the challenge of Arsenic contamination in soils [29][30][31][32][33].…”
Section: A Justification Of the Studymentioning
confidence: 99%